Lewa wolna - Mackiewicz, Jozef (Londyn : Kontra, 1987)
A novel about the destiny of the Poles under the communist rulers.
Reprint of the second ed. published by Kontra in 1981.
"First published in 1965 by Polska Funday'a Kulturalna".
Keywords: Poland -- History -- 1945- -- Fiction